The Effectiveness of Tourism Videos to Improve The Tenth Grade Students’ Speaking Achievement in SMKN 6 Palembang - Bella Syebania; Jaya Nur Iman (Universitas Indo Global Mandiri, 2018)
AbstractThis research was aimed to find out whether there was significant improvement on speaking achievement of the tenth grade students of SMKN 6 Palembang after being taught by using the Tourism Videos and to find out whether there was significant mean difference on speaking achievement between the students who were taught by using Tourism Videos and those who were not. This research applied experimental research design. The sample of this research were 31 students of SMKN 6 Palembang and divided into experimental and control groups. The results of this study were calculated by using SPSS. The research finding showed that the mean score of pretest of experimental group was 56,84 improved to 80,32. And the mean difference of posttest between experimental and control group was 2.129 and the mean difference of speaking improvement between the pretest and posttest within the experimental group was 23,484. The research findings revealed that the teaching of speaking improved the students’ speaking achievement due to having received the treatment using Tourism Videos. Hence, that there was significant improvement on speaking achievement in the experimental group and there was significant mean difference between the students who were taught by using Tourism Videos and those who were not.Keywords : Improving speaking skill, speaking skill, tourism video AbstrakPenelitian ini bertujuan untuk mengetahui apakah ada peningkatan yang signifikan terhadap prestasi berbicara siswa kelas X SMKN 6 Palembang setelah diajar dengan menggunakan Video Pariwisata dan untuk mengetahui apakah ada perbedaan rata-rata yang signifikan pada prestasi berbicara antara siswa yang diajarkan dengan menggunakan Video Pariwisata dan mereka yang tidak. Penelitian ini menggunakan desain penelitian eksperimental. Sampel penelitian ini adalah 31 siswa SMKN 6 Palembang dan dibagi menjadi kelompok eksperimen dan kontrol. Hasil penelitian ini dihitung dengan menggunakan SPSS. Temuan penelitian menunjukkan bahwa skor rata-rata pretest dari kelompok eksperimen adalah 56,84 meningkat menjadi 80,32. Dan perbedaan rata-rata posttest antara eksperimental dan kelompok kontrol adalah 2,129 dan perbedaan rata-rata peningkatan berbicara antara pretest dan posttest dalam kelompok eksperimen adalah 23.484. Temuan penelitian mengungkapkan bahwa pengajaran berbicara meningkatkan prestasi berbicara siswa karena telah menerima perlakuan menggunakan Video Pariwisata. Oleh karena itu, bahwa ada peningkatan yang signifikan pada prestasi berbicara dalam kelompok eksperimen dan ada perbedaan rata-rata yang signifikan antara siswa yang diajar dengan menggunakan Video Pariwisata dan mereka yang tidak.Kata kunci: Meningkatkan keterampilan berbicara, keterampilan berbicara, video pariwisata